About the Cover. Issue 1 (1st June 2021) - Ball, Andrew J.; Rybin, Aleksandr
Abstract : The cover of this issue of Screen Bodies features the digital work "Crypto Queen" by restlessperson (Aleksandr Rybin), which the artist has minted as an NFT. We spoke with Rybin about the subject matter of his work, connections between digital and analog art, and the future of NFTs. His work is available on KnownOrigin.